Failure of Continuous Improvement initiatives in manufacturing environments: a systematic review of the evidence. (23rd February 2017) - McLean, Richard S.; Antony, Jiju; Dahlgaard, Jens J.
Abstract : Continuous Improvement initiatives put in place the necessary elements to allow an organisation to identify and implement improvements on an ongoing basis. Structured approaches to quality and process improvement started with total quality managenment, and developed with Lean Manufacturing, Six Sigma, and Lean Six Sigma. Despite the benefits these can bring, Continuous Improvement efforts are consistently reported to have a high failure rate. Research, however, regularly focuses on success factors rather than directly addressing failures, and as a result, failure factors are currently fragmented. The objective of this paper is to provide a systematic literature review detailing why Continuous Improvement initiatives within manufacturing environments may fail. The paper describes the systematic review protocol followed and reasoning associated. From the 72 journal articles selected, it is evident that initiatives can fail due to a multitude of individual variables. The main contribution of the paper is the grouping of these under eight core themes: Motives & Expectations, Culture & Environment, Management Leadership, Implementation Approach, Training, Project Management, Employee Involvement Levels, and Feedback & Results. The findings provide insight regarding the complexity of organisational change involving Continuous Improvement implementation. The need for future research to develop the themes into a framework is also discussed.